A Novel Synthesis of ZnO Nanoflower Arrays Using a Lift-Off Technique with Different Thicknesses of Al Sacrificial Layers on a Patterned Sapphire Substrate - Hsien-Wei Tseng; Ching-Shan Wang; Fang-Hsing Wang; Han-Wen Liu; Cheng-Fu Yang (Nanomaterials, 2022)
A novel method to synthesize large-scale ZnO nanoflower arrays using a protrusion patterned ZnO seed layer was investigated. Different thicknesses of aluminum (Al) film were deposited on the concave patterned sapphire substrate as a sacrificial layer. ZnO gel was layered onto the Al film as a seed layer and OE-6370HF AB optical glue was used as the adhesive material. A lift-off technique was used to transfer the protrusion patterned ZnO/AB glue seed layer to a P-type Si <100> wafer. The hydrothermal method using Zn(CH3COO)2 and C6H12N4 solutions as liquid precursors was used to synthesize ZnO nanoflower arrays on the patterned seed layer. X-ray diffraction spectra, field-effect scanning electron microscopy, focused ion beam milling (for obtaining cross-sectional views), and photoluminescence (PL) spectrometry were used to analyze the effects that different synthesis times and different thicknesses of Al sacrificial layer had on the properties of ZnO nanoflower arrays. These effects included an increased diameter, and a decreased height, density (i.e., number of nanorods in μm−2), total surface area, total volume, and maximum emission intensity of PL spectrum. We showed that when the synthesis time and the thickness of the Al sacrificial layer were increased, the emission intensities of the ultraviolet light and visible light had different variations.